Tindak Tutur Direktif Pada Kegiatan Masyarakat Pesisir di Desa Botubarani Kabupaten Bone Bolango: Penelitian - Alwi Kakoe, Moh.; Ntelu, Asna; Salam (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Speech acts are a way of communicating that considers both language use and situational aspects. They are classified into locutionary, illocutionary, and perlocutionary acts. This study aims to describe the forms and types of directive speech acts in community activities in Botubarani Village, Bone Bolango Regency. Using a qualitative descriptive method, data were collected from conversations between speakers and interlocutors, including tourists at the whale shark tourism site. The findings reveal 40 instances of directive speech acts categorized into five types: warnings, recommendations, advice, requests, and prohibitions. The study concludes that the forms and types of directive speech acts in the village align with the applied theories and methods.